CO2 and heat energy transport by enhanced fracture permeability in the Monterotondo Marittimo-Sasso Pisano transfer fault system (Larderello Geothermal Field, Italy). (November 2022) - Taussi, Marco; Brogi, Andrea; Liotta, Domenico; Nisi, Barbara; Perrini, Maddalena; Vaselli, Orlando; Zambrano, Miller; Zucchi, Martina
Highlights: CO2 degassing and faults/fractures in the Monterotondo-Sasso Pisano transfer fault. CO2 flux, temperature, volumetric fracture intensity and permeability survey. Discrete Fracture Network (DFN) modeling to reconstruct the fault architecture. CO2 flux and steam change in relation to the architecture of the fault damage zone. Increased degassing rates evidence enhanced structural permeability. Abstract: Carbon dioxide is one of the most important gasses naturally released from geothermal systems. Establishing the processes and pathways that regulate the CO2 diffuse degassing can provide valuable information for exploration and exploitation purposes of geothermal reservoirs. In this work, a high-resolution CO2 flux (with records up to 2927 g m –2 d –1 ) and soil temperature (with records up to 98.8 °C) survey was carried out along with detailed fracture parameters measurements in a selected area of the Monterotondo Marittimo-Sasso Pisano transfer fault (Larderello geothermal system, Tuscany, Italy). The main aim was to define the behavior of diffuse CO2 through the fault system and investigate how the soil CO2 flux and steam change with respect to the architecture of the fault damage zone (i.e., volumetric fracture intensity, permeability, and persistence of the fractures). The presence of multiple populations of CO2 flux suggested that three different transport mechanisms control soil degassing: i) purely diffusive, ii) mixed diffusive-advective, and iii) purely advective, characterized by efflux values of <20, between 20 and 300 and >300 g m –2 d –1, respectively. The spatial distribution of these fluxes well agrees with the fracture distribution and features of the Jurassic radiolarite (Diaspri Fm) dissected by NNE-striking faults. Areas with high CO2 emissions are indeed able to reveal major upflow areas from deep reservoirs through deep-reaching permeable fault zones. The interaction between pre-existing fractures and fracture-related fault-zone locally enhances the secondary rock permeability as highlighted by the correlation between Discrete Fracture Network (DFN) modeling and advective flux. Eventually, by normalizing the CO2 output to the fault strip (1350 m 2 ), a release of CO2 equal to ∼155 t d –1 km –2 was estimated.